2008
DOI: 10.1002/prot.21961
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding energetics and stability of banana lectin

Abstract: The unfolding pathway of banana lectin from Musa paradisiaca was determined by isothermal denaturation induced by the chaotrope GdnCl. The unfolding was found to be a reversible process. The data obtained by isothermal denaturation provided information on conformational stability of banana lectin. The high values of DeltaG of unfolding at various temperatures indicated the strength of intersubunit interactions. It was found that banana lectin is a very stable and denatures at high chaotrope concentrations only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…It is only at extreme temperature of 600 K that the RMSD increases steadily. It attains an average value of 8 Å between 200 and 400 ps simulation time, after which it rises to a value of 10 Å. Simulation at 500 K for 500 ps makes the protein lose its compactness to an extent, but the unfolding process occurs only at 600 K. From the RGYR plot, we observe a small change of only 1 Å from 19 Å at 300 K to 20 Å at 600 K. It indicates that the dimer is reasonably compact even at 600 K, consistent with experimental observation (23) that strong perturbations are required to destabilize the Banlec dimer. However, it is to be noted that fluctuations in RGYR has considerably increased at 600 K, indicating perturbations from its native structure.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…It is only at extreme temperature of 600 K that the RMSD increases steadily. It attains an average value of 8 Å between 200 and 400 ps simulation time, after which it rises to a value of 10 Å. Simulation at 500 K for 500 ps makes the protein lose its compactness to an extent, but the unfolding process occurs only at 600 K. From the RGYR plot, we observe a small change of only 1 Å from 19 Å at 300 K to 20 Å at 600 K. It indicates that the dimer is reasonably compact even at 600 K, consistent with experimental observation (23) that strong perturbations are required to destabilize the Banlec dimer. However, it is to be noted that fluctuations in RGYR has considerably increased at 600 K, indicating perturbations from its native structure.…”
Section: Resultssupporting
confidence: 87%
“…In a separate study, we have investigated the structural stability of Banlec in the presence of chaotropes. It was observed that despite a small interfacial area, Banlec displays substantial conformational stability in the presence of chaotropic agents (23). It is, however, not a good system for studying thermal denaturation experimentally as it aggregates immediately at its melting temperature which is quite high; therefore, high‐temperature MD simulations were performed.…”
Section: Introductionmentioning
confidence: 99%
“…The second part of this study was to compare the chemical stability of various states of BL. Chemical stability of BL determined at neutral pH using guanidine hydrochloride has already been reported showing that BL is quite stable [46]. In the present study, chemical stability of BL was examined at both monomeric (pH 2.0) as well as dimeric (pH 7.4) state using urea as a denaturant.…”
Section: Discussionmentioning
confidence: 87%
“…Urea is widely exploited as chaotrops for checking the stability of proteins at neutral as well as acidic pH [47][49]. The equilibrium unfolding of BL in the presence of urea was found to be a cooperative process in which the protein molecule undergoes unfolding without stabilization of any partially unfolded intermediate at both pH values (7.4 and 2.0) similarly no intermediates were found in the case of GdnHCl denaturation of same lectin at pH 7.4 [46]. Oligomeric proteins have usually more chemical stability than its monomer form because of additional non-covalent and covalent interactions [50].…”
Section: Discussionmentioning
confidence: 97%
“…The results are consistent with the differential scanning calorimetry (DSC) analysis that BanLec-1 had a transition maximum temperature ( Tm ) of 60.8 °C. [ 21 ] The agglutination activity of rBanLec was stable in a broad pH range from 4 to 12, and was gradually lost when pH values were below 4 or above 12, which indicated that rBanLec was stable under alkali conditions. These results supported the observations that BanLec-1 is a stable dimer in solution,[ 12 ] and the stability of the dimer may result from strong hydrogen bonds and water bridges at the interface between the two subunits of BanLec-1.…”
Section: Resultsmentioning
confidence: 99%